Notopterol Ameliorates Hyperuricemia-Induced Cardiac Dysfunction in Mice - Qian Wang; Dewei Peng; Bingyu Huang; Lintong Men; Tao Jiang; Shengqi Huo; Moran Wang; Junyi Guo; Jiagao Lv; Li Lin (Pharmaceuticals, 2023)
Notopterol is a naturally occurring furanocoumarin compound found in the root of Notopterygium incisum. Hyperuricemia involves the activation of chronic inflammation and leads to cardiac damage. Whether notopterol has cardioprotective potential in hyperuricemia mice remains elusive. The hyperuricemic mouse model was constructed by administration of potassium oxonate and adenine every other day for six weeks. Notopterol (20 mg/kg) and allopurinol (10 mg/kg) were given daily as treatment, respectively. The results showed that hyperuricemia dampened heart function and reduced exercise capacity. Notopterol treatment improved exercise capacity and alleviated cardiac dysfunction in hyperuricemic mice. P2X7R and pyroptosis signals were activated both in hyperuricemic mice and in uric acid-stimulated H9c2 cells. Additionally, it was verified that inhibition of P2X7R alleviated pyroptosis and inflammatory signals in uric acid-treated H9c2 cells. Notopterol administration significantly suppressed expression levels of pyroptosis associated proteins and P2X7R in vivo and in vitro. P2X7R overexpression abolished the inhibition effect of notopterol on pyroptosis. Collectively, our findings suggested that P2X7R played a critical role in uric acid-induced NLRP3 inflammatory signals. Notopterol inhibited pyroptosis via inhibiting the P2X7R/NLRP3 signaling pathway under uric acid stimulation. Notopterol might represent a potential therapeutic strategy against pyroptosis and improve cardiac function in hyperuricemic mice.